Trends of exhaust emissions from gasoline motor vehicles in the metropolitan area of Mexico city. (11th May 2004) - Schifter, I.; Diaz, L.; Avalos, S.; Vera, M.; Mejia, I.; Reyes, F.; Lopez-Salinas, E.
Light duty gasoline vehicles account for most of CO, hydrocarbons and NOx emissions to the urban environment in the metropolitan area of Mexico City. In order to ameliorate air pollution, several control measures have been imposed in the last decade, such as: up-grade of gasoline's quality, stringent environmental standards, and catalytic converters. On the other hand and from the beginning of 2001, Tier I emission standards became mandatory for all new model year sold in the country. Car manufacturers in Mexico do not guarantee the performance of their exhaust emissions systems for a given mileage. In this work, we present results on brand new vehicles that indicate that NOx emission factors, though they are within the Tier I standard, deteriorate rapidly with the travelled distance (mileage).